Corruption, South African Multinational Enterprises and Institutions in Africa - Luiz, John M. (Journal of business ethics, 2014)
We examine the responses of South African multinational enterprises (MNEs) to corruption in African markets in the context of institutional voids. Corruption is a source of uncertainty and additional transactional costs for MNEs and it necessitates a strategic response. The research employs a qualitative study of a sample of MNEs with experience in internationalising into Africa. The results indicate that corruption in African markets is pervasive and closely associated with the institutional voids in these countries. MNEs see themselves as ‘institution takers’ responding to countries’ institutional makeup at the organisational and individual level but fail to fully appreciate their impact on institutions both positively and negatively. Rather MNEs focus on strategic responses at the organisational level to address corruption operationally in the host country. We add to the existing literature by providing a dynamic framework of the complex webs of association between institutions, MNEs and corruption in conditions of economic underdevelopment. The research suggests that MNEs do not need to get caught in a vicious cycle whereby they perpetuate corruption in conditions of underdevelopment and institutional voids but instead can contribute towards a virtuous cycle through which they institutionalise ethical foundations.